STRATEGIES OF ADOLESCENTS’ DELINQUENT BEHAVIOR AND REASONS FOR ITS EMERGENCE - Mikhalchenkova, Natalya; Bolshakov, Sergey; Bolshakova, Yuliya (Revista Inclusiones, 2020)
The article presents an analysis of factors and conditions leading to the emergence of delinquency and deviant behavior in adolescents. The social role of the family institution is investigated, family styles of behavior and decision-making are examined, and conclusions are made on the effect of family structure on adolescents’ deviant behavior. The role of social norms including a wide variety of views and accepted socially significant standards of behavior is also disclosed in the study. The authors examine the social objectives of resolving the problems of deviances and delinquency in adolescents and analyze the effect of family and the quality of family relationships on adolescent’s psychological and emotional stability.